Evaluation of the impact of genetic linkage in forensic identity and relationship testing for expanded DNA marker sets. (January 2017) - Tillmar, Andreas O.; Phillips, Chris
Highlights: A biostatistical tool for analyzing the overall effect of linkage on likelihood calculations in various forensic genetic case scenarios is presented. The tool is provided as a command script via the open-source platform R and is prepared with reference data for over 40 STRs and 140 SNPs. The tool can be used during marker selection and the design of new marker panels or applied to existing marker sets to examine the effect of linkage on a case-by-case basis. Studies of existing forensic marker panels show the impact of linkage is generally small, but may be more considerable in individual cases. Abstract: Advances in massively parallel sequencing technology have enabled the combination of a much-expanded number of DNA markers (notably STRs and SNPs in one or combined multiplexes), with the aim of increasing the weight of evidence in forensic casework. However, when data from multiple loci on the same chromosome are used, genetic linkage can affect the final likelihood calculation. In order to study the effect of linkage for different sets of markers we developed the biostatistical tool ILIR, (Impact of Linkage on forensic markers for Identity and Relationship tests). The ILIR tool can be used to study the overall impact of genetic linkage for an arbitrary set of markers used in forensic testing. Application of ILIR can be useful during marker selection and design of new marker panels, as well as being highly relevant for existing marker sets as a way to properly evaluate the effects of linkage on a case-by-case basis. ILIR, implemented via the open source platform R, includes variation and genomic position reference data for over 40 STRs and 140 SNPs, combined with the ability to include additional forensic markers of interest. The use of the software is demonstrated with examples from several different established marker sets (such as the expanded CODIS core loci) including a review of the interpretation of linked genetic data.